Response of plasma and gastrointestinal melatonin, plasma cortisol and activity rhythms of European sea bass (Dicentrarchus labrax) to dietary supplementation with tryptophan and melatonin - Herrero, M. J; Martínez, F. J; Míguez, J. M; Madrid, J. A (Journal of comparative physiology. B, Biochemical, systemic, and environmental physiology, 2007)
Melatonin is an effective antioxidant, immunostimulant, gonadal maturating regulator and antistress indoleamine that may be potentially useful for fish farmers. We have explored two possible ways of increasing plasma melatonin levels through the diet: direct melatonin supplementation (ME diet) and supplementation with the melatonin precursor tryptophan (TRP diet). To this end, a group of sea bass was fed a commercial diet (STD diet) at a regular time for 16 days, after which plasma, intestine, and bile samples were taken at four different time points: 120 min before, and 15, 180 and 480 min after feeding. Locomotor activity, intestinal and biliary melatonin, and plasma melatonin, serotonin and cortisol levels were measured. This same sampling process and analyses were also carried out after feeding sea bass TRP diet or ME diet for 1 week. Our results show that melatonin, but not tryptophan supplementation of the diet increases plasma, intestine and bile levels of melatonin. Plasma serotonin levels, on the other hand, were increased by dietary tryptophan, but not by melatonin, confirming the availability of supplemented tryptophan for serotonin synthesis. Both treatments were equally effective in reducing the high cortisol levels observed with the STD diet.